Impact of Global Climate Change on Agricultural Development - Abbasov, Anar Fazil (Acta Universitatis Danubius. Œconomica, 2024)
The process of globalization significantly influences not only the system of international relations and socio-economic development but also has profound effects on the environment and natural geographic processes. This is most evident against the backdrop of global climate change. The most significant manifestations of global climate change are first felt in agriculture. Research indicates that global climate change, primarily in the context of global warming, results in the destruction of green spaces, water resource shortages, and other harmful phenomena, adversely affecting agricultural development. The harmful effects of global climate change on agriculture primarily lead to a decline in soil fertility and negatively impact the growth of crops due to warmer air masses. It is important to note that climate change, when considered independently, creates numerous problems for the development of agriculture not only in individual countries but globally. Global warming primarily causes a reduction in precipitation, leading to longer drought periods, which negatively affects agricultural productivity. Consequently, this results in a decrease in agricultural production. Therefore, mitigating the harmful effects of global climate change can play a significant role in fostering positive developments in agriculture. Investment is necessary to neutralize the impacts of global climate change on agriculture. Additionally, developing new crop strategies and implementing innovative technologies for cultivating specific plants are crucial. Notably, Azerbaijan has substantial potential for agricultural production due to its favorable natural climate conditions and diverse soil types. Azerbaijan’s eleven climate zones provide suitable conditions for the production of various crops. Historically, including during the Soviet era, Azerbaijan’s comparative advantages in agriculture were utilized to meet the food needs of the former Soviet Union’s central regions. The production of early vegetables played a significant role in satisfying the food demands of these regions. Global climate change does not only result in global warming but also increases precipitation in certain areas, which can negatively impact the quality of agricultural products. Changes in climate conditions also affect the quality of agricultural products. Rising temperatures can significantly reduce the nutritional value of agricultural products and, in some cases, adversely affect their taste and quality. Climate change leads to the degradation of land and agricultural areas, reducing soil fertility and the efficiency of agricultural production. This paper presents scientifically grounded and practically significant proposals for mitigating the harmful effects of global climate change on agriculture.